On Complexity - Morin, Edgar (New Yersey Hampton press, 2008)
Edgar Morin is director of studies emeritus at France's Centre National de la Recherche Scientifique and president of the Association pour la Pensee Complexe. He is the author of over thirty books and numerous articles on topics ranging from scientific method and anthropology to politics and popular culture. Richard Howard, poet and critic, teaches at the School of Arts at Columbia University. He has translated many books of French criticism, including works by Roland Barthes, Michel Foucault, and Tzvetan Todorov. His most recent translations include Absinthe: A Novel and The Charterhouse of Parma.